Overexpression of ALDH21 from Syntrichia caninervis Moss in Upland Cotton Enhances Fiber Quality, Boll Component Traits, and Physiological Parameters during Deficit Irrigation. Issue 2 (1st March 2019) - Yang, Honglan; Zhang, Dawei; Zhang, Daoyuan; Bozorov, Tohir A.; Abdullaev, Alisher A.; Wood, Andrew J.; Wang, Jiancheng; Li, Xiaoshuang; Zhao, Jinyi
Abstract : Plants have evolved complex molecular, cellular, and physiological mechanisms to respond to environmental stressors. Genetic manipulationhas represented an important potential method for improving water deficit tolerance in crops. Aldehyde dehydrogenases are involved in cellular responses to oxidative stress to protect against a variety of environmental stressors. The Syntrichia caninervis Mitt. ALDH21 gene plays a role in plant responses to abiotic stresses, and overexpression of this gene in tobacco ( Nicoiana tabacum L.) and cotton ( Gossypium hirsutum L.) decreases their sensitivity that improves tolerance to drought and salt stresses. To test the possibility that transgenic cotton constitutively expressing ScALDH21 may be suitable for cultivating under water deficit conditions, phenotype, physiological response, and yield of transgenic ScALDH21 cotton were measured in managed treatment plots and under field conditions. Overexpression of ScALDH21 in cotton resulted in higher net photosynthetic rate, less cellular damage, more cellular protective compounds, and enhanced growth compared with nontransgenic (NT) cotton under drought stress in managed treatment plots. Yield of transgenic cottons under deficit irrigation condition was increased above that for NT plants measured under full irrigation conditions. Under field conditions, transgenic cotton yield increased ∼10.0% under full irrigation and ∼18.0% under deficit irrigation conditions compared with NT. Fiber quality of transgenic cotton lines was also improved compared with NT under both full and deficit irrigation. These results suggest that transgenic ScALDH21 cotton is a viable candidate material for improving crop yields in water‐limited agricultural production systems.